2021
DOI: 10.3390/atmos12020232
|View full text |Cite
|
Sign up to set email alerts
|

Projected Characteristic Changes of a Typical Tropical Cyclone under Climate Change in the South West Indian Ocean

Abstract: During 2 January 2014, Cyclone Bejisa passed near La Réunion in the southwestern Indian Ocean, bringing wind speeds of 41 m s−1, an ocean swell of 7 m, and rainfall accumulations of 1025 mm over 48 h. As a typical cyclone to impact La Réunion, we investigate how the characteristics of this cyclone could change in response to future warming via high-resolution, atmosphere–ocean coupled simulations of Bejisa-like cyclones in historical and future environments. Future environments are constructed using the pseudo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 55 publications
(78 reference statements)
1
9
0
Order By: Relevance
“…In this section, we recall some key features of tropical cyclone TC Bejisa, which detailed description can be found in Pianezze et al [26]. TC Bejisa is representative of the storms that regularly affect Reunion Island and has been chosen for its relatively common meridian track, average intensity and speed of displacement [27]. In this study we focus on the period between 1 January 00 UTC and 2 January 12 UTC, which corresponds to the period it passed to the closest to Reunion Island.…”
Section: Case Study: Tropical Cyclone Bejisamentioning
confidence: 99%
“…In this section, we recall some key features of tropical cyclone TC Bejisa, which detailed description can be found in Pianezze et al [26]. TC Bejisa is representative of the storms that regularly affect Reunion Island and has been chosen for its relatively common meridian track, average intensity and speed of displacement [27]. In this study we focus on the period between 1 January 00 UTC and 2 January 12 UTC, which corresponds to the period it passed to the closest to Reunion Island.…”
Section: Case Study: Tropical Cyclone Bejisamentioning
confidence: 99%
“…This strategy relies on the exploitation of unprecedented high-resolution global climate simulations [32], as well as of mesoscale coupled simulations to estimate the impact of climate change on the intensity, behavior, and consequences of TCs at the scale of a given territory. Examples of results obtained from such high-resolution model runs are discussed in [33,67] (both in this Special Issue).…”
Section: Climate Componentmentioning
confidence: 99%
“…They showed that using a 1D coupling (Meso-NH coupled to a 1D ocean mixed layer model) does not enable to reproduce the intensity and structure of surface ocean cooling compared to composite observations, while a 3D coupled model (Meso-NH coupled to the 3D NEMO model) does. Finally, an ocean-atmosphere configuration with km-scale grid spacing was implemented to investigate how the characteristics of a typical TC like Bejisa would evolve in the context of climate change [67]. The pseudo global warming method was used to construct future environments: perturbations computed from six Coupled Model Intercomparison Project 5 (CMIP5) climate models were added to historical analyses from ECMWF.…”
Section: Modeling Studies Of Tropical Cyclones Dumile (2013) and Bejisa (2014)mentioning
confidence: 99%
“…One of the goals of the climate component of RNR-CYC was thus to evaluate the future evolution of TC activity in the SWIO. While high-resolution simulations performed with global models are used to anticipate the global evolution of the TC activity [13], a pseudo global warming procedure is implemented in the coupled OWA model described in Section 2 to evaluate the modifications of the TC structure and impacts in a modified oceanic and atmospheric environment [67].…”
Section: Climate Projection Of Tropical Cyclone Activity In the Swiomentioning
confidence: 99%
See 1 more Smart Citation